Pediatic nuclear medicine exposure to radiation - Duarte, Ana Cristina (2017)
Introduction - In general, the procedures used in Nuclear Medicine (NM), involve a lower exposure to ionizing radiation when compared to the exposure of background radiation, which is 2.4 mSv. The importance and diagnostical value of these procedures, when performed properly, outweigh the potential risk of radiation exposure. Recently, the use of these innovative imaging techniques has increased exponentially, so there is a particular interest in understanding how these exposures affect the pediatric age since children are more sensitive to them than adults. Methods - A descriptive study based on a systematic review of the literature through PubMed, 6 articles were included that respect, at least, one of the following criteria: pediatric exposure in NM, the effects of low doses of radiation and doses optimization. The keywords used in the PubMed: radiation exposure, paediatric nuclear medicine, risk. And the application of Boolean markers AND, OR, NOT. Results - The risk of the consequences due to radiation exposure is greater in younger individuals. The administered activity is a parameter of significant importance in the risk of radiation exposure in NM and communication can facilitate the understanding of this exposure and the associated risks. Conclusions - Exposure to radiation due to procedures used in NM doesn’t present an increasing risk to the normal occurrence of malignant diseases and its correct communication to the child and their family is important to ensure the safety of the patient and those who surround them during these procedures. Any activity is calculated according to the child's weight and height, taking into accounts the ALARA principle, in order to obtain a better diagnosis with the minimum required activity and consequent radiation exposure.